Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's solve the equation [tex]\(3x^2 - 27 = 0\)[/tex] step by step using square roots.
1. Move the constant term to the other side of the equation:
We start with the given equation:
[tex]\[ 3x^2 - 27 = 0 \][/tex]
Add 27 to both sides to isolate the [tex]\(x^2\)[/tex] term:
[tex]\[ 3x^2 = 27 \][/tex]
2. Divide both sides by the coefficient of [tex]\(x^2\)[/tex]:
To isolate [tex]\(x^2\)[/tex], divide both sides of the equation by 3:
[tex]\[ x^2 = \frac{27}{3} \][/tex]
Simplify the right-hand side:
[tex]\[ x^2 = 9 \][/tex]
3. Take the square root of both sides to solve for [tex]\(x\)[/tex]:
To solve for [tex]\(x\)[/tex], take the square root of both sides of the equation. Remember that taking the square root yields two solutions, a positive and a negative:
[tex]\[ x = \pm \sqrt{9} \][/tex]
Simplify the square root:
[tex]\[ x = \pm 3 \][/tex]
So, the solutions to the equation [tex]\(3x^2 - 27 = 0\)[/tex] are:
[tex]\[ x = 3 \quad \text{and} \quad x = -3 \][/tex]
Thus, the correct answers are [tex]\(\pm 3\)[/tex].
1. Move the constant term to the other side of the equation:
We start with the given equation:
[tex]\[ 3x^2 - 27 = 0 \][/tex]
Add 27 to both sides to isolate the [tex]\(x^2\)[/tex] term:
[tex]\[ 3x^2 = 27 \][/tex]
2. Divide both sides by the coefficient of [tex]\(x^2\)[/tex]:
To isolate [tex]\(x^2\)[/tex], divide both sides of the equation by 3:
[tex]\[ x^2 = \frac{27}{3} \][/tex]
Simplify the right-hand side:
[tex]\[ x^2 = 9 \][/tex]
3. Take the square root of both sides to solve for [tex]\(x\)[/tex]:
To solve for [tex]\(x\)[/tex], take the square root of both sides of the equation. Remember that taking the square root yields two solutions, a positive and a negative:
[tex]\[ x = \pm \sqrt{9} \][/tex]
Simplify the square root:
[tex]\[ x = \pm 3 \][/tex]
So, the solutions to the equation [tex]\(3x^2 - 27 = 0\)[/tex] are:
[tex]\[ x = 3 \quad \text{and} \quad x = -3 \][/tex]
Thus, the correct answers are [tex]\(\pm 3\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.